Uji Efektivitas Antihiperurisemia Ekstrak Etanol Kencur (Kaempferia galanga L.) dan Jahe Hitam (Kaempferia parviflora) terhadap Tikus yang Diinduksi Jus Hati Ayam dan Potassium Oxonate - Wikantyasning, Erindyah Retno; Wahyuni, Arifah Sri; Julianti, Tri Budi; Putri, Nastity Zhahwa Amalia; Astuti, Devi Dwi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Hyperuricemia is caused by excessive production and/or poor elimination of uric acid. Kencur (Kaempferia galanga L.) and black ginger (Kaemperia parviflora) can be utilised as antihyperurisemic alternatives because their flavonoids block xanthin oxidase (XO). The study determine the efficacy of black ginger ethanol extract (EEJH) as an in vivo antihyperuricemic agent. This research was conducted to determine the effectiveness of kencur ethanol extract (EK) dan black ginger ethanol extract (EEJH) as an antihyperuricemia in vivo. A complete random design used involving 32 mice in 8 groups. Negative control (CMC Na 0.5%); positive control (Allopurinol 10 mg/kgBW); EK and EEJH respectively 12.5; 25; and 50 mg/kgBW. Hyperurisemia was induced by chicken liver juice 4 mL/200 gBB p.o. and potassium oxonate 250 mg/kgBB i.p. UA monitoring was carried out before induction, 0, 7, and 14 days after treatment. Tukey post hoc tests and ANOVA were used to evaluate the data. The results indicate that both of EK and EEJH can reduced UA (p<0.05) however the reduction is significant with Allopurinol (P<0.05). Thus, it can be inferred that the EK and EEJH have potential for enhanced antihyperurysemic in decreasing the UA.